Synthesis and Theoretical Studies of 1,3,3,5,5-Pentachloro-1-mono-(2-amidopyridin)cyclotriphosphazene - A. Ahmed, Safaa (Asian Journal of Chemistry, 2012)
1,3,3,5,5-Pentachloro-1-mono(2-amidopyridine)cyclotriphosphazene was prepared from hexachlorocyclotriphosphazene and 2-amino pyridine in acetone. The structure of the white crystals of the prepared compound was elucidated by the X-ray diffraction and supported by the FTIR and 1H, 13C, 31P NMR spectroscopy. Since the X-ray diffraction is not accurate in detecting the position of the hydrogen atoms, Density functional theory (B3LYP) was used to study the structure and the spectroscopic properties of the compound and its tautomers that belong to the hydrogen tautomerism. Calculations have shown that the isomer in which the hydrogen attached to the nitrogen atom of the amido nitrogen that attached to the pyridine ring has the lowest energy and that comes in accordance with 1H NMR and FTIR spectroscopy. Potential energy curve with calculated activation energy is reported.